L’argument juridique dans les négociations internationales : l’exemple de la commission franco-britannique de 1750 à 1755 - Ternat, François (Presses universitaires de Rennes, 2018)
The Treaty of Aix-la-Chapelle that ended the War of Austrian Succession in 1748 threw into relief the link between European and colonial issues. It returned the European claims in North America and in the West Indies to the statu quo ante bellum settled by the Treaty of Utrecht of 1713. A boundary commission was established to study the claims, to determine which areas were considered as belonging to the British or to the French Crowns, and to define clear boundaries separating the colonial dominions. Not only an episode of Anglo-French rivalry, these inter-war years took place in the middle of the Age of Enlightenment, which sanctioned the idea of balance of powers.Intellectual, legal and doctrinal thinking about the European rights claimed or exercised at sea and abroad on lands under imperial influence had been developed during the peace commission in Paris (1750-1755), whose aim was to resolve boundary disputes between the two Crowns’ pretensions to lands also largely occupied by Aboriginal peoples. Important historical knowledge and juridical arguments were exchanged and discussed between the French and the British commissioners, which in turn generated new understandings and doctrinal approaches expressed in various proposals to assert European sovereignty on land and at sea. More specifically, this article examines the process involving the First Nations of America in the diplomatic proposals argued from both sides by the Crowns’ agents. Despite their failure and the outbreak of war in 1756, these negotiations can be seen as attempts to regulate colonial and maritime disputes through international agreements and as experiences by both Courts of diplomacy in faraway lands.